2020
DOI: 10.20900/agmr20200024
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Induced DNA Damage as an Underlying Cause of Aging

Abstract: Oxidative or redox stress arises from the generation of reactive oxygen species (ROS) as a by-product of oxygen utilization. ROS-mediated damage to DNA accumulates over time and leads to irreversible changes in cellular functions and integrity associated with aging phenotypes. Here, we discuss the contribution of ROS-induced DNA damage to aging and the important role of deficiencies in DNA repair pathways that counteract this damage. We elaborate on the relationship of aging with mutagenesis and epigenetics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
6
1
Order By: Relevance
“…However, we found that DNA damage levels were negatively correlated with age for some genes. At face value, our results appear to contradict multiple reports documenting an overall decline in DNA repair with age and, more generally, a strong causal relationship between DNA damage and aging (Campisi, 2013 ; Chen et al., 2020 ; Hoeijmakers, 2009 ; Maynard et al., 2015 ; Ou & Schumacher, 2018 ; Robert & Wagner, 2020 ; Yousefzadeh et al., 2021 ). However, the following interpretative caveats must be considered.…”
Section: Discussioncontrasting
confidence: 95%
“…However, we found that DNA damage levels were negatively correlated with age for some genes. At face value, our results appear to contradict multiple reports documenting an overall decline in DNA repair with age and, more generally, a strong causal relationship between DNA damage and aging (Campisi, 2013 ; Chen et al., 2020 ; Hoeijmakers, 2009 ; Maynard et al., 2015 ; Ou & Schumacher, 2018 ; Robert & Wagner, 2020 ; Yousefzadeh et al., 2021 ). However, the following interpretative caveats must be considered.…”
Section: Discussioncontrasting
confidence: 95%
“…DNA damage induced by oxidative stress, whether by acute injury (as in ischemia/reperfusion( 42 )), or during gradual and stochastic accumulation of genomic errors (as in aging( 43, 44 )), drives cell and tissue dysfunction. Nuclear DNA damage leads to DNA leakage into the cytosol, kickstarting cGAS-STING( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ABCA7 LoF neurons, mitochondrial stress may result from catabolism of accumulated triglycerides through increased fatty acid oxidation and result in the detected elevation in ROS ( 62 ). These ROS may then cascade down, producing DNA damage and inflammation ( 6366 ) observed in ABCA7 LoF ( Fig. S11 ).…”
Section: Discussionmentioning
confidence: 99%